On the Use of Language in the Anti-Capitalist Debate - Poole, Eve (Journal of business ethics, 2005)
The anti-capitalist debate has traditionally drawn up battle lines between oppressed individuals on the one hand, and an oppressive system on the other. While this has high rhetorical value, it is based on imprecise use of language. The language confuses an amoral system with im/moral agents but at the same time uses anthropomorphic language to lend capitalism moral agency. This inevitably leads to a confused debate. Given that all opponents of capitalism want the reformation of what they see as a flawed system, precision in the use of the language employed would move the debate into arenas of action, and thus the debate is more likely to generate change.